Aberrant histone methylation in the patients with immune thrombocytopenia. (May 2014) - Zhao, Haifeng; Xue, Feng; Xu, Jianfen; Fang, Zhi
Abstract The aim of the present study was to investigate alterations in histone methylation in patients with primary immune thrombocytopenia (ITP). Global histone H3K4/H3K9 methylation in CD4+ T cells from 35 ITP patients and 15 healthy controls were measured using the EpiQuikTM global histone H3K4/H3K9 methylation assay kits. The mRNA expression of SUV39H1, SUV39H2 and EZH2 were detected by real-time quantitative polymerase chain reaction (RT-PCR). The results showed that global histone H3K9 hypomethylation in CD4+ T cells of active ITP, compared with ITP in remission and controls, while the global histone H3K4 methylation were not significantly different between ITP patients and healthy controls. The expression of EZH2 and SUV39H2 were significantly down-regulated in active ITP patients, when compared with ITP in remission and controls. There were not different between ITP patients and controls in the expression SUV39H1. In conclusion, the aberrant histone methylation was involved in the pathogenesis of ITP.